1990
DOI: 10.1111/j.1472-765x.1990.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial activity of smoke from different woods

Abstract: Smoking of food is one common form of food preservation. Ethanol solutions of smoke from burning white mangrove (Auicennia nitida), mahogany (Khaya sp.) and abura (Mitrayyna ciliata) inhibited the growth of Escherichia coli, Staphylococcus aureus and Saccharomyces cereuisiae. Smoke from red mangrove (Rhizophora racemosa) and Alstonia boonei inhibited the growth of Staphylococcus aureus and Saccharomyces cerevisiae but not Escherichia coli. Smoke from burning black afara (Terminalia ivorensis) inhibited the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…These organic compounds can have stimulatory, inhibitory or no impact on microbial growth [70,129]. As seen in Table 2, some biochars have high volatile matter contents.…”
Section: Box 1 Volatile Organic Compounds Sorbed On Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…These organic compounds can have stimulatory, inhibitory or no impact on microbial growth [70,129]. As seen in Table 2, some biochars have high volatile matter contents.…”
Section: Box 1 Volatile Organic Compounds Sorbed On Biocharmentioning
confidence: 99%
“…Potential hypotheses explaining these effects have focused mainly on abiotic interactions (e.g., pH changes, bulk density decreases, alterations in nutrient availability, water retention increases, biochar structure, and soil structure alterations), providing additional microbial habitat, as well as promotion of colonization by arbuscular mycorrhizal fungi [65,66]. Recent research has also indicated the potential role of volatiles (sorbed or produced; Box 1) in the suppression of microbial nitrification rates and other microbial processes [67][68][69][70][71][72], which could also influence biotic biochar Microbial degradation of charcoal has been noted for some time [73,74] along with recent observations of wooddecaying fungi capable of degrading (solubilizing) lowgrade coals (e.g., lignite) [75][76][77]. These observations would suggest the role of fungi in the biological degradation of biochars, with the primary pathway through extracellular enzymes.…”
Section: Microbial Degradation Of Biocharmentioning
confidence: 99%
“…have shown to inhibit microbial growth with Khaya spp. exhibiting the most pronounced antimicrobial effect (Asita and Campbell, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial effect of smoke condensates from different woods against Saccharomyces cerevisiae, Staphylococcus aureus and Escherichia coli has been demonstrated (Asita & Campbell, 1990). However, the extract of Eriocephalus punctulatus has been shown to possess antimicrobial, anti-inflammatory, and antioxidant activities, and also inhibit acetylcholinesterase (Njenga & Viljoen, 2006;Samie & Nefefe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Asita and Campbell (1990) with some modification. The smoke condensed in an inverted glass funnel which was placed above the open top.…”
Section: Methodsmentioning
confidence: 99%